FNIRS-based functional connectivity signifies recovery in patients with disorders of consciousness after DBS treatment. (March 2023) - Shu, Zhilin; Wu, Jingchao; Li, Haitao; Liu, Jinrui; Lu, Jiewei; Lin, Jianeng; Liang, Siquan; Wu, Jialing; Han, Jianda; Yu, Ningbo
Highlights: fNIRS-based functional analysis quantifies DBS neuromodulation on DOC patients. A greater improvement of consciousness was observed in patients with trauma. Brain communication efficiency can serve as a DOC functional marker. Abstract: Objective: While deep brain stimulation (DBS) has proved effective for certain patients with disorders of consciousness (DOC), the working neural mechanism is not clear, the response varies for patients, and the assessment is inadequate. This paper aims to quantify the DBS-induced changes of consciousness in DOC patients at the neural functional level. Methods: Ten DOC patients were included for DBS surgery. The DBS target was the right centromedian-parafascicular (CM-pf) nuclei for four patients and the bilateral CM-pf nuclei for six patients. Functional near-infrared spectroscopy (fNIRS) was taken to measure the neural activation of patients, in parallel with Coma Recovery Scale-Revised (CRS-R), before the DBS surgery and one month after. The fNIRS signals were recorded from the frontal, parietal, and occipital lobes. Functional connectivity analysis quantified the communication between brain regions, area communication strength, and global communication efficiency. Linear regression analysis was conducted between the changes of indices based on functional connectivity analysis and the changes of the CRS-R index. Results: Patients with trauma (n = 4) exhibited a greater increase of CRS-R scores after DBS treatment compared with patients with hemorrhage (n = 4) and brainstem infarction (n = 2). Global communication efficiency changed consistently with the CRS-R index (slope = 57.384, p < 0.05, R 2 =0.483). No significant relationship was found between the changes of area communication strength of six brain lobes and the changes of the CRS-R index. Conclusions: The cause of DOC is essential for the outcome of DBS treatment, and brain communication efficiency is a promising functional marker for DOC recovery. Significance: fNIRS-based functional connectivity analysis on brain network signifies changes of consciousness in DOC patients after DBS treatment.